Dammarane and apotirucallane triterpenoids from the stem bark of Melia toosendan and their antibacterial activities. (24th September 2022) - Shao, Li-Li; Liu, Han-Fei; Lou, Hua-Yong; Ma, Feng-Wei; Chen, Chao; Li, Jin-Yu; Pan, Wei-Dong
Abstract: Eight previously undescribed triterpenoids, including four dammarane-type triterpenoids, named meliasenans A−D (1 –4 ), four apotirucallane-type triterpenoids, named meliasenans E−H (5 –8 ), along with nine known analogues (9 –17 ) have been isolated from the stem bark of Melia toosendan . The structures of the new compounds were elucidated by IR, HRESIMS, 1D, 2D NMR, electronic circular dichroism (ECD) calculations, as well as single-crystal X-ray diffraction analysis. The results of bioassay showed that the new compounds 7 and 8 exhibited potential antibacterial effect on Pseudomonas solanacearum and Bacillus gasoformans, with MIC values of 117.2 μg mL −1 and 118 μg mL −1, respectively. Moreover, 8 and 11 showed apparent antibacterial activities against Bacillus subtilis (ATCC 6051) with MIC values of 118 μg mL −1 and 92.1 μg mL −1, respectively. Graphical abstract: Eight previously undescribed and nine known triterpenoids were isolated from the stem bark of Melia toosendan . Image 1 Highlights: Eight undescribed and nine known triterpenoids were isolated from Melia toosendan. Their structures were elucidated by spectroscopic methods and X-ray diffraction. Meliasenan G and Meliasenan H showed weak antibacterial activity.